Environmental Policy Strategy as a Moderator in the Relationship Between Green Investment, CSR Investment, and Financial Performance - Mauzani, Laura; Karim, Ilmi Fathul; Torres, Eduardo Luis (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to analyze the role of environmental policy as a moderator in the relationship between green investment, CSR investment, and corporate financial performance. As awareness of sustainability issues increases, companies are increasingly faced with pressure to invest in green initiatives and corporate social responsibility (CSR) programs. However, the impact of these investments on financial performance often depends on the environmental policy framework implemented. This research uses a quantitative approach with secondary data analysis from companies operating in capital-intensive and high-risk industries. The results indicate that strong environmental policies can strengthen the relationship between green investment and financial performance, as well as have a positive impact on the influence of CSR investment on financial performance. Conversely, in environments with weak policies, the relationship tends to be weaker and inconsistent. These findings provide new insights into the importance of environmental policy as a determining factor in maximizing the benefits of green and CSR investments for companies. Therefore, companies need to consider environmental policies when designing investment strategies to ensure optimal results in both financial and sustainability aspects.